An Empirical Examination of Organisational Trust Recovery: Influences and Implications. Issue 4 (31st July 2018) - Kharouf, Husni; Lund, Donald J.
Abstract : Building trust between organizations and their customers has attracted considerable academic research attention. However, research into the trust recovery process, following a trust violation has occurred is limited in comparison. This study investigates the trust recovery process by examining six recovery approaches which organizations can employ to repair trust. Six trust recovery approaches were first examined using canonical correlation. Our research investigates the impact of these six trust recovery approaches following two different types (integrity and competence) of trust violations. We assessed the influence of these approaches on customer loyalty, satisfaction and perceptions of organizational trustworthiness using structural equation modelling. Results suggest that apology and denial are the most effective approaches to repairing trust, and that the effect of these recovery approaches on customer satisfaction and loyalty are mediated by organizational trustworthiness.